Pengaruh Leader-Member Exchange, Persepsi Dukungan Organisasional, Budaya Etnis Papua dan Organizational Citizenship Behavior, terhadap Kinerja Pegawai pada Sekda Provinsi Papua - Kambu, Arius (Jurnal Aplikasi Manajemen, 2012)
The purpose of this study was to analyze and determine the effect of Leader-Member Exchange, the perception of organizational support and cultural (ethnic culture of papua) on organizational citizenship behavior and its impact on employee performance. Access the sample consisted of 300 employees who have a chance papua ethnic working in SEKDA Papua. This study uses descriptive analysis to determine the characteristics of respondents for each indicator variable. Meanwhile, to test the relationship between variables used methods of SEM analysis with AMOS approach 6. The results of this study have shown that the Leader-Member Exchange have not been able to establish good organizational citizenship behavior, and improve employee performance. Furthermore the perception of organizational support, cultural (ethnic culture papua) are partially able to form organizational citizenship behavior and employee performance. In addition, the results suggest that in order to improve labor discipline and work ethic better employees, leaders must consider the factor of local culture, communication and work commitments.